Educação de jovens e adultos: um estudo acerca dos princípios políticos e pedagógicos que conduziram a proposta educacional do Movimento Brasileiro de Educação – MOBRAL (1967-1985) - Prado, Mariana Lemos do (2017)
The Brazilian Literacy Movement (MOBRAL) created during the military regime (1964-1985) by the brazilian law n° 5.379 of 15/12/1967, was one of the most extensive and complex adult education program developed in the country. For this study, an elaborated analysis were made of the political and pedagogical principles, methodologies and ideals that led the main programs of MOBRAL, with emphasis on functional literacy. With the aim of highlighting the ideological representations of MOBRAL, a bibliographical and documentary research washeld based upon documentation and educational legislation of the period (1967-1985); statutes and basic institutional documents; academic researches; publications of the Ministry of Education and the teaching materials for support of MOBRAL. The administrative structure and the sophistication of their information, logistics and supervisory systems demonstrate the centralisation, hierarchisation and rigidity control of the processes. The technocratic orientation of the Movement is assigned to the influence of the Institute for Applied Economic Research (Ipea), in particular for the work of Arlindo Lopes Corrêa,that stands as founder, manager and representative of the MOBRAL. Côrrea was na intellectual Who sought to mediate the political and ideological unity of the Movement and legitimize his work for the people. The campaigns, teaching materials, principles and objectives of the programs spread the ideas of progress, patriotism and community participation, combining the propaganda on behalf of government with the elation of MOBRAL and his deeds. In addition to not getting the expected results, the MOBRAL contributed to reinforce the prejudice against the illiterate, blaming them for the country's educational delay and valuing their negative aspects. The critical evaluation of the educational proposal of MOBRAL, considering the political, economic and social context of your time, emphasize the contradiction of an authoritarian and excluding regime that proclaimed the universalization and democratization of education. Keywords: MOBRAL. Adult education. Functional literacy. Dictatorship. Political and pedagogical principles.